0809 Feasibility and Acceptability of Light Therapy to Increase Energy in Adolescents and Young Adults Newly Diagnosed with Cancer. (12th April 2019) - Crabtree, Valerie M; Zhang, Hui; Wang, Fang; Brigden, Jane; MacArthur, Erin; Russell, Kathryn; Wilson, Matthew W; Pappo, Alberto
Abstract: Introduction: Fatigue is one of the most consistent, distressing symptoms reported by adolescent/young adult (AYA) oncology patients. Bright white light (BWL) has been shown to combat fatigue in adult oncology, but no interventions have been developed to reduce fatigue in AYA oncology patients. We therefore designed a study to estimate the feasibility and acceptability of BWL to decrease fatigue in AYA patients with newly diagnosed solid tumors. Methods: Participants were randomized to receive dim red light (DRL, n = 24) or BWL (n = 27) via LiteBook® (retrofitted with adherence monitors) for 30 minutes upon awakening daily for eight weeks. Feasibility was defined as at least 65% of participants consenting and at least 50% utilizing the light on at least 50% of days. Of the 70 patients approached, 55 consented and randomized. Four participants never used the light book and were deemed passive refusals; final n = 51 (mean age = 15.96 ± 2.41, range = 12-22 years; 49% female). To determine acceptability, treatment-emergent extreme headache or eye strain were evaluated. Side effects were assessed weekly via modified Systematic Assessment for Treatment Emergent Effects (SAFTEE). Participants also completed mood, quality of life, and fatigue measures. Results: 72.96% of those approached consented and participated. 67% used the light for at least 15 minutes on at least 50% of the days. Mean adherence was 57% of days on study (CI 47.57-62.1%). At each stopping point, BWL demonstrated no significantly greater number of extreme treatment-emergent effects than DRL. Conclusion: This is the first study to evaluate feasibility and acceptability of light therapy to reduce fatigue in AYA oncology patients, and we found that this therapy is feasible and acceptable. Measures of fatigue, quality of life, and mood will be evaluated as secondary analyses to provide preliminary support for an effectiveness trial. Given the severity of fatigue experienced by AYA oncology patients and the lack of evidence-based interventions to ameliorate this symptom, our approach promises new research opportunities for symptom management. Support (If Any): ALSAC